IMPLEMENTASI KEBIJAKAN PROGRAM PEMBERDAYAAN KOMUNITAS ADAT TERPENCIL (KAT) DALAM MENANGGULANGI KEMISKINAN DI LOKASI SEKULIT DESA MUNGGU KECAMATAN LONGKALI KABUPATEN PASER - Edwin Kurniawan; Aji Ratna Kusuma; Adam Idris (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
The purpose of this study is to describe and analyse the Implementation of Remote Indigenous Community Empowerment Program In Tackling Poverty. The data are taken from the informants and key informants and supported by secondary data. The data then is analysed using interactive model that were developed by Milles, Huberman and Saldana.